Embrace Empathy: Exploring the Spectrum of Understanding - Pericleous, Vicky (My University, 2024)
The exhibition is organized by the Vorres Museum, a member and collaborator of the EMPACT group, and includes artists and artworks created as part of various actions carried out by all collaborating entities from all participating countries, along with Greek artists invited to enrich the exhibition with their own perspective on the program’s major themes. The exhibition is curated by Olga Daniylopoulou and is accompanied by the publication of a high-quality and content-rich catalog. Additionally, the Vorres Museum is organizing an educational program related to the artists and artworks participating in the exhibition. 26 artist in total are presented at the Vorres Museum in this group Show; 17 have collaborated in some action with one of the 7 European partners of the EMPACT project. Additionally, works of 9 Greek artists were selected by the curator to intersperse with their works, addressing the issues discussed by the EMPACT project in the context of its actions. The exhibition includes works from various collaborative programs, workshops and residencies:
Keywords: Arts; Exhibitions; empathy & sustainability; understanding Empathy; Art synergies; Cultural landscapes & Empathy; pedagogy through art; Nature & Empathy